2020
DOI: 10.1111/cla.12407
|View full text |Cite
|
Sign up to set email alerts
|

A species‐level total evidence phylogeny of the microteiid lizard family Alopoglossidae (Squamata: Gymnophthalmoidea)

Abstract: Alopoglossidae is a family of Neotropical lizards composed of 23 species allocated in two genera (Alopoglossus and Ptychoglossus). There is a lack of knowledge about the phylogenetic relationships and systematics of this family. Published phylogenies that include alopoglossid species have very low taxon coverage within the family, and are usually based on limited character sampling. Considering these shortcomings, we infer the phylogenetic relationships of Alopoglossidae-including all but one species in the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 75 publications
(89 reference statements)
0
12
0
1
Order By: Relevance
“…[21]. Dashed lines represent phylogenetic relationships by * Reference [18], ** Reference [19] and *** Reference [20].…”
Section: Sex Chromosome Diversity In Lizards: Qualitative and Quantitative Distribution Of Available Datamentioning
confidence: 99%
See 2 more Smart Citations
“…[21]. Dashed lines represent phylogenetic relationships by * Reference [18], ** Reference [19] and *** Reference [20].…”
Section: Sex Chromosome Diversity In Lizards: Qualitative and Quantitative Distribution Of Available Datamentioning
confidence: 99%
“… Distribution of TSD and male (M-GSD) and female (F-GSD) genetic sex determination on lizard phylogenetic relationships redrawn from Reference [ 21 ]. Dashed lines represent phylogenetic relationships by * Reference [ 18 ], ** Reference [ 19 ] and *** Reference [ 20 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The genus differs from Ptychoglossus Boulenger (1890) (the other genus belonging to the Alopoglossidae family; Goicoechea et al, 2016) in having keeled scales on the forelimbs (vs. smooth forelimb scales) and rhomboid, laterally imbricating dorsal scales (vs. parallel-sided dorsal scales) (Harris, 1994). A few phylogenetic studies, based on genetic data, morphological data, or both, have targeted species of Alopoglossidae (Pellegrino et al, 2001;Castoe et al, 2004;Goicoechea et al, 2016;Morales et al, 2020;Ribeiro-J ´unior et al, 2020). Nonetheless, the current taxonomic status of both species and genera in the family is still controversial.…”
mentioning
confidence: 99%
“…Nonetheless, the current taxonomic status of both species and genera in the family is still controversial. For example, Morales et al (2020) recently suggested the need to synonymize Ptychoglossus with Alopoglossus. Moreover, a revision of A. angulatus resulted in the delimitation of no less than eight candidate species (Ribeiro-J ´unior et al, 2020).…”
mentioning
confidence: 99%